Cómo propiciar el aprendizaje autónomo mediante una clase integr al en el marco del Modelo Pedagógico UPC - Viale Tudela, Héctor Ernesto (2015)
This article presents the design of the Math Level 0 course aligned with the Educational  Model of the UPC and developed under the structure proposed by 'MATE'.  The  phrase 'Less is more' that  gives  name to this article describes  a  philosophical  concept which is applicable to the classroom where the teacher only intervenes when it  is necessary. In this context, the student has the major role. 'Less  is More' requires the student  accessing knowledge  with enthusiasm, which will  occur if the student has a major role in the teachinglearning system.  The  teachers  are  one more  resource in the  classroom and while  the  knowledge that  should be acquired is important, the learning process learnt by the student on their own is paramount.  It is expected in 'Less is More' that the teacher favours the learning of the students in an environment of tolerance and respect  and it is demanded from the teacher to create  a  varied and stimulating learning experience instead of imparting knowledge  in a  patronizing way.